2003
DOI: 10.1152/ajplung.00167.2002
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinase inhibition by Batimastat attenuates pulmonary hypertension in chronically hypoxic rats

Abstract: Chronic hypoxia induces lung vascular remodeling, which results in pulmonary hypertension. We hypothesized that a previously found increase in collagenolytic activity of matrix metalloproteinases during hypoxia promotes pulmonary vascular remodeling and hypertension. To test this hypothesis, we exposed rats to hypoxia (fraction of inspired oxygen = 0.1, 3 wk) and treated them with a metalloproteinase inhibitor, Batimastat (30 mg/kg body wt, daily ip injection). Hypoxia-induced increases in concentration of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 51 publications
1
38
1
Order By: Relevance
“…Our previous experiments showed that the first week of hypoxic exposure is crucial for the development of HPH (2,6,10). It seems that the discrepancies in the course of recovery are mainly due to differences in the duration and type of hypoxia (continual or intermittent, normobaric or hypobaric) resulting in the various degree of tissue radical injury and different PAP values at the end of exposure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous experiments showed that the first week of hypoxic exposure is crucial for the development of HPH (2,6,10). It seems that the discrepancies in the course of recovery are mainly due to differences in the duration and type of hypoxia (continual or intermittent, normobaric or hypobaric) resulting in the various degree of tissue radical injury and different PAP values at the end of exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Lungs were filled with formol solution and then the lung sections were stained with the hematoxylin resorcinfuchsin. Percentage of hypertensive double-laminated prealveolar vessels was counted as described previously (6). 73 …”
Section: Methodsmentioning
confidence: 99%
“…They found an overt increase in matrix metalloproteinase-2 and matrix metalloproteinase-9 activity of the lung in acute pulmonary embolism and then treatment with L-arginine brought relief in pulmonary hypertension and caused reduction of matrix metalloproteinase-2 and matrix metalloproteinase-9 activity. On the same way, batimastat, a specific matrix metalloproteinase inhibitor, were tested by different researchers and batimastat formed a similar beneficial effects in chronically hypoxic rats with pulmonary hypertension (33).…”
Section: Matrix Metalloproteinases and Tissue Inhibitors In Pulmonarymentioning
confidence: 97%
“…Finally it is seen that pharmacological inhibitors of matrix metalloproteinases such as doxycycline, zinc chelators and batimastat have been used as diagnostic and therapeutic tools in cancer, autoimmune and cardiovascular diseases (32,33). Therefore, the following question comes to mind for our study, wonder if the medications used by patients had impact on the matrix metalloproteinases levels?…”
Section: Matrix Metalloproteinases and Tissue Inhibitors In Pulmonarymentioning
confidence: 98%
“…Increased MMP-2 activity in the pulmonary vessels of hypoxic rats was shown to be associated with the severity of PH (Frisdal et al, 2001). In addition, Herget et al (2003) reported that inhibition of MMP activity attenuated pulmonary vascular remodeling as well as hypertension in chronically hypoxic rats, and suggested that the increased MMP activity might represent a substantial factor mediating the effect of hypoxia on the development of PH. Another study by Lepetit et al (2005) demonstrated an imbalance between MMP-3 and TIMP-1 expression and an increase in MMP-2 expression in pulmonary arterial smooth muscle cells from patients with IPAH.…”
Section: Pulmonary Vascular Remodelingmentioning
confidence: 99%